An economic analysis of dismissal legislation: Determinants of severance pay in West Germany - Laszlo Goerke; Markus Pannenberg (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2009)
Severance pay is a vital part of employment protection legislation (EPL). We investigate the incidence and level of severance pay for dismissed employees. Our theoretical model predicts that not only the law and its interpretation by labour courts but also the costs of a suit have an impact. Using West German panel data for 1991-2006, we find that the employees' costs resulting from a suit and the legal determinants of such transfers affect the incidence of severance payments. In contrast, their level only varies with legal regulations. Our results imply that the strictness of EPL in Germany varies with extra-legal factors like employees' financial constraints.
Keywords: J65; K31; C23; C24; 330; employment protection legislation; labour law; severance pay; survey data; Abfindung; Arbeitsrecht; Gerichtliche Prozesskosten; Alte Bundesländer